Inter- and intra-individual covariations of hemodynamic and oscillatory gamma responses in the human cortex - Zaehle, Tino; Fründ, Ingo; Schadow, Jeanette; Thärig, Stefanie; Schoenfeld, Mircea A.; Herrmann, Christoph S. (Frontiers in Human Neuroscience, 2009)
The time course of local field potentials displaying typical discharge frequencies in the gamma frequency range highly correlates with the BOLD signal in response to rotating checkerboard stimuli in animals. In humans, oscillatory gamma-band responses (GBRs) show strong inter-individual variations in frequency and amplitude but considerable intra-individual reliability indicating that individual gamma activity reflects a personal trait. While the functional role of these GBRs is still debated, investigations combining EEG–fMRI measurements provide a tool to obtain further insights into the underlying functional architecture of the human brain and will shed light onto the understanding of the dynamic relation between the BOLD signal and the properties of the electrical activity recorded on the scalp. We investigated the relation between the hemodynamic response and evoked gamma-band response (eGBR) to visual stimulation. We tested the hypothesis that the amplitude of human eGBRs and BOLD responses covary intra-individually as a function of stimulation as well as inter-individually as a function of gamma-trait. 17 participants performed visual discrimination tasks during separate EEG and fMRI recordings. Results revealed that visual stimuli that evoked high GBRs also elicited strong BOLD responses in the human V1/V2 complex. Furthermore, inter-individual variations of BOLD responses to visual stimuli in the bilateral primary (Area 17) and secondary (Area V5/MT) visual cortex and the right hippocampal formation were correlated with the individual gamma-trait of the subjects. The present study further supports the notion that neural oscillations in the gamma frequency range are involved in the cascade of neural processes that underlie the hemodynamic responses measured with fMRI.